Type species fixation of the genus Abloxurina Johnson, 1992 (Lepidoptera: Lycaenidae: Theclinae) - Prieto, Carlos; Lorenc-Brudecka, Jadwiga (Zootaxa, 2014)
The goal of this paper is to clarify the status and identity of the type species of the lycaenid genus Abloxurina Johnson, 1992 so that the name can be used correctly in future taxonomic work. Abloxurina was originally typified with Thecla amatista Dognin, 1895. However, the specimen examined and illustrated by Johnson (1992) to diagnose the genus was an individual of Penaincisalia ismaeli Busby & Hall, 2005, an undescribed species at that time. Consequently, Johnson’s original typification was based on a misidentification. In order to make Abloxurina available, its type species is fixed under Article 70.3.2 of the International Code of Zoological Nomenclature (1999) as P. ismaeli.